Impact of processing conditions on the rehydration kinetics and texture profile of freeze-dried carbohydrates sources - Vitor Andre Silva Vidal; Sara Slettemark Juel; Kirill Mukhatov; Ida-Johanne Jensen; Jørgen Lerfall (Journal of Agriculture and Food Research)
Rehydration is a complex process related to the structural changes occurring during dehydration. Knowledge about rehydration processes is essential to improve quality and contribute to developing new dehydrated products with desirable characteristics. Carbohydrates are essential macronutrients and could be affected by several physical and chemical changes during processing steps. The aim of the present study was to investigate the effects of boiling, freeze-drying, and the subsequent rehydration process on the rehydration kinetics of different carbohydrate sources (potato, rice, white pasta, and whole-grain pasta) and texture profile. The effects of boiling time, freeze-drying, rehydration time, and temperature (20, 50, and 90 °C) on the carbohydrate samples were investigated through analyses of moisture content, rehydration capacity, and texture profile. Furthermore, the Zugarramurdi and Lupín empirical model was used to describe the rehydration kinetics. According to the results obtained, the processing parameters and combinations of boiling times, freeze-drying, and rehydration of carbohydrate samples significantly impact the rehydration kinetics and texture profile of the final product. Additionally, the Zugarramurdi and Lupín empirical model was found to be suitable for predicting the moisture content during the rehydration process of these type of samples. The results obtained in this study would be useful for accurately determine the processing conditions to produce freeze-dried carbohydrate foods with desirable rehydration characteristics and texture properties.